Productive performance of Arapaima gigas in temperate climate ponds - Ganoza C., Francisco (2023)
The study monitored the productive performance of the paiche (Arapaima gigas) for 30 months under temperate climate conditions on the Central Coast of Peru. After 40 days of acclimatization and with 80% survival, the fish (n: 32, weight: 44 ± 34 g, length: 17.6 ± 4.9 cm) were transferred to a greenhouse pool (8 fish/m3) and fed at 5 % of their body weight with a diet of 60% balanced trout food and 40% deboned and gutted fresh fish. After 15 months under a greenhouse and with 62% survival, the fish (n: 20, weight: 4.3 ± 1.0 kg, length: 77.3 cm) were transferred to an open-air excavated earth pond (6.9 fish/m3) and fed fresh fish at 5% of body weight. The water temperature fluctuated between 23.2 and 26.0 °C in the greenhouse, and between 23.0 and 24.6 °C in the environmental pond, being up to 18% lower in temperature with respect to the minimum water temperature in its natural habitat. At 32 months of age, the paiche reached 1.23 m in length and 16.89 kg in weight. Weight gains fluctuated between 3.4 and 20.9 g/d in the greenhouse and 8.4 and 74.6 g/d in the environmental pond. In the cold season, fish were characterized by showing higher feed consumption, but lower weight gains, reflected in poor feed conversion rates. Mortality of 38% was recorded only in the greenhouse stage. The productive parameters of the paiche in temperate climate conditions were lower than those achieved in its tropical climate habitat; however, the less variable weight gain in the greenhouse and the more efficient feed conversion in warm seasons suggest that its cultivation would be viable under greenhouse conditions.